DAKWAH STYLISH DI ERA DIGITAL DAN KONTESTASI OTORITAS KEAGAMAAN: STUDI KASUS HANAN ATTAKI DAN USTADZ SELEBRITAS INDONESIA - Deviolina Fitria Kholisari (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The phenomenon of stylish da'wah popularized by Hanan Attaki and celebrity preachers in Indonesia demonstrates a shift in da'wah authority from traditional ulama (Islamic scholars) to more personal and interactive digital figures, utilizing social media to reach a wider audience, especially the younger generation. The popularity of these preachers presents challenges to religious legitimacy, where da'wah messages are often influenced by image and persona appeal, leading to new negotiations between Islamic values, popular culture, and traditional authority. The qualitative approach based on literature review in this study reveals that digital da'wah is not merely a communication innovation but also a dynamic space that reflects the transformation and complexity of contemporary da'wah in Indonesia.